PEMODELAN KARAKTERISITIK DENIAL OF SERVICE ATTACK MELALUI ANALISIS DATA TRAFIK - Wijaya, Octavianus; Jusak, Jusak; Sukmaaji, Anjik (Journal of Control and Network Systems, 2014)
DoS is one example of attacks that can disrupt the infrastructure of computer networks, this type of attack has a typical pattern, where in each attack will send a number of data packets continuously to attack the target. DoS Attack consists of UDP, PING and SYN Flood Attack. This study aims to get a mean, relative frequency, parameter values, the probability distribution, plot the data and the value of MSE. Subsequently analyzed using statistical methods, and modeling to estimate the parameters in the form of a probability distribution. The probability distribution is composed of a gamma distribution, lognormal distribution and weibull distribution. By using this model, it can be shown that the DoS Attack characteristic of UDP Attack and SYN Flood Attack are much closer to the lognormal distribution than Gamma the distribution or Weibull distribution. On the other hand, the distribution of the PING flood attack resembles the gamma distribution.